Design of a state observer using decay rate LMI constraints for fault detection in mechanical systems - Koroishi, Edson Hideki [UNESP]; De Melo, Gilberto Pechoto [UNESP]; Assunção, Edvaldo [UNESP] (My University, 2010)
Nowadays, one of the most important concerns for many companies is to maintain the operation of their systems without sudden equipment break down. Because of this, new techniques for fault detection and location in mechanical systems subject to dynamic loads have been developed. This paper studies of the influence of the decay rate in the design of state observers using LMI for fault detection in mechanical systems. This influence is analyzed by the performance index proposed by Huh and Stein for the condition of a state observer. An example is presented to illustrate the methodology discussed.
Keywords: Decay rate; Faults detection; LMI; Performance index; State observers; Performance indices; State observer; Decay (organic); Dynamic loads; Linear matrix inequalities; Machine design; Mechanical engineering; Mechanics; State estimation; Fault detection